Alkaloid Extract from Chimarrhis cymosa as a Corrosion Inhibitor for C38 Steel in 1M Hydrochloric Acid: Electrochemical and XPS Studies - Mahado Said-Ahmed; Mounim Lebrini (Metals)
The inhibitory effect of the alkaloid extract from Chimarrhis cymosa on C38 steel corrosion in 1M HCl was examined through electrochemical investigations. An inhibition efficiency of 90% was achieved with 200 mg/L of the alkaloid extract from Chimarrhis cymosa at 25 °C. Potentiodynamic polarization revealed that the extract acts as a mixed-type inhibitor. Nyquist plots showed that an increase in the concentration of the alkaloid extract from Chimarrhis cymosa led to an increase in charge-transfer resistance and a decrease in double-layer capacitance, resulting in enhanced inhibition efficiency. The adsorption of inhibitor molecules followed the Langmuir adsorption isotherm. XPS analysis confirmed the formation of an inhibitor layer on the steel surface containing the Chimarrhis cymosa alkaloidic extract.